The artistic spirit of cities: How cities influence artists' agency. (November 2022) - Kaddar, Merav; Barak, Nir; Hoop, Marie; Kirchberg, Volker; de Shalit, Avner
Abstract: This paper examines the reciprocal relationship between artists and cities by analyzing how cities influence artists' critical engagement. We hypothesize that a set of specific urban conditions suggests distinct forms of artistic engagement, which we call the artistic spirit of the city. Based on qualitative fieldwork in four cities in Germany and Israel, we explore how cities influence the self-perception, motivation, and practice of the artists who work and live in them. We found that artists are indeed highly influenced by the particular spirit or the intrinsic logic of the city in which they live and work, and they are embedded within the city's particular socio-political and spatial structures, which in turn influence their outlooks and visions as artistic city-zens. Highlights: We introduce the concept artistic spirit of cities to capture how cities impact urban artistic practices. Cities influence artistic practices by virtue of their institutions, municipal policies and budgets, and civic networks. Cities influence the self-perception, motivations, and practices of artists who work and live in them. Cities influence artists' political participation, contestation of power, and political efficacy. We demonstrate this dynamic in four cities: Jerusalem, Tel Aviv-Jaffa, Hamburg, and Hanover.